HYPERTHYROIDISM DURING PREGNANCY LEADS TO THE PREMATURE DELIVERY - Uhood abbas obed; ZAINAB SABEEH ABD UL RAZZA (Scholar Express Journals, 2023)
Thyroid hormones are very essential for fetal development and brain growth. A pituitary gland secretes thyroid stimulating hormone (TSH) which in turn regulates Secretion of thyroid hormones. These hormones are T4 (thyroxine) and T3 (triiodothyronoinine). In the current study, effect of hyperthyroidism during pregnancy on prenatal outcome was evaluated. A pregnant woman (n=50) with unusual serum thyroid hormone levels was considered for disease group. The age match women (n=50), without unusual serum thyroid hormone levels, were enrolled in the healthy group. Their serum thyroid hormones and thyroid stimulating hormone (TSH) were evaluated and correlated with the pregnancy outcome.
Keywords: Hyperthyroidism; Thyroid hormones; Thyroid stimulating hormone